2018
DOI: 10.1002/mus.26055
|View full text |Cite
|
Sign up to set email alerts
|

Toenail mercury Levels are associated with amyotrophic lateral sclerosis risk

Abstract: Biomarker data show that ALS is associated with increased with mercury levels, which were related to estimated methylmercury intake via fish. Replication of these associations in additional populations is warranted. Muscle Nerve, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 36 publications
1
29
1
Order By: Relevance
“…Even if several recent studies analysed the use of nails as biomarkers of different minerals and nETE and to relate their concentration to some diseases risk such as amyotrophic lateral sclerosis, children obesity, hearing loss and acute promyelocytic leukaemia (Karatela et al, 2018;Chen et al, 2018;Li et al, 2018;Xu et al, 2018;Andrew et al, 2018;White et al, 2018). In the present study, no relation was found by between nETE fingernail, dietary exposure and thyroid cancer risk.…”
Section: Study Limitationscontrasting
confidence: 65%
“…Even if several recent studies analysed the use of nails as biomarkers of different minerals and nETE and to relate their concentration to some diseases risk such as amyotrophic lateral sclerosis, children obesity, hearing loss and acute promyelocytic leukaemia (Karatela et al, 2018;Chen et al, 2018;Li et al, 2018;Xu et al, 2018;Andrew et al, 2018;White et al, 2018). In the present study, no relation was found by between nETE fingernail, dietary exposure and thyroid cancer risk.…”
Section: Study Limitationscontrasting
confidence: 65%
“…Only 10% of nail mercury represents mercury derived from inorganic sources, such as dental amalgam in non-occupationally exposed populations (19). In our prior clinic-based work in northern New England, we observed higher toenail Hg levels in 46 ALS patients, compared with n ¼ 66 controls who did not have neurodegenerative illness (p ¼ 0.024) (20). In the present analysis, we sought to validate this mercury finding in an independent U.S. cohort using a case-control comparison.…”
Section: Introductionmentioning
confidence: 65%
“…One possible link between personality traits and ALS is that the premorbid personality differences seen in people with ALS could lead to behaviors that are reported to be risk factors for the disease (Figure ). Connections between personality traits and ALS risk factors could, for example, exist between extraversion‐linked smoking (Buczkowski et al, ), a reported risk factor for ALS (Armon, ); extraversion‐linked risk‐taking behavior (Levenson, ), which could lead to the increased numbers of head injuries reported in ALS (Schmidt, Kwee, Allen, & Oddone, ); conscientiousness‐linked physical exercise (Malinauskas, Dumciene, Mamkus, & Venckunas, ), another suggested risk factor for ALS (Beghi et al, ); conscientiousness‐linked low alcohol intake (Lunn, Nowson, Worsley, & Torres, ), which is associated with ALS (de Jong et al, ); conscientiousness‐linked adherence to dietary advice on increased fish intake (Lunn et al, ), which may be a risk factor for ALS due to mercury ingestion (Andrew et al, ); and either conscientiousness, openness, neuroticism, or agreeableness all of which can influence choice of occupation (Zhao & Seibert, ), since certain occupations have been associated with ALS (Sutedja et al, ). These potential links imply that some of the lifestyle habits and choices thought to be risk factors for ALS may not be risk factors per se, but rather the consequence of an underlying, substantially genetically determined, personality type.…”
Section: Discussionmentioning
confidence: 99%